2002
DOI: 10.2307/3285502
|View full text |Cite
|
Sign up to set email alerts
|

The Filarial Endosymbiont Wolbachia sp. Is Absent from Setaria equina

Abstract: Wolbachia sp. was first reported in filarial nematodes over 25 yr ago. Today, much research is focused on the role of these bacteria in filarial worm biology. The filarial symbionts are closely related to arthropod symbionts, which are known to modify host reproduction and biology through various mechanisms. Similarly, it has been suggested that Wolbachia sp. is essential for long-term survival and reproduction of filariae. We report that Wolbachia sp. 16S rDNA was not found in the equine filarial nematode Set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Litomosoides sigmodontis was studied by transmission electron microscopy and by immunohistochemistry using antiendobacterial heat shock protein-60 antisera (Hoerauf et al 1999). However, this bacterium has not been observed in Acantocheilonema vitae, Onchocerca flexuosa Wedl, 1856, Loa loa Guyot 1778, and Setaria equine (Bandi et al 1998;Henkle-Dührsen et al 1998;Buttner et al 2003;Chirgwin et al 2002).…”
Section: Discussionmentioning
confidence: 95%
“…Litomosoides sigmodontis was studied by transmission electron microscopy and by immunohistochemistry using antiendobacterial heat shock protein-60 antisera (Hoerauf et al 1999). However, this bacterium has not been observed in Acantocheilonema vitae, Onchocerca flexuosa Wedl, 1856, Loa loa Guyot 1778, and Setaria equine (Bandi et al 1998;Henkle-Dührsen et al 1998;Buttner et al 2003;Chirgwin et al 2002).…”
Section: Discussionmentioning
confidence: 95%
“…Two examined Setaria species, S. cervi (Dattta et al, 2007) and S. equina (Chirgwin et al, 2002), have been reported to be free of Wolbachia. In this study, S. digitata was also identified as an additional species of Setaria that is free of Wolbachia.…”
Section: Discussionmentioning
confidence: 97%
“…S. digitata is a member of the Setaria genus of the Setariidae family of the Filarioidea superfamily; therefore, the loss of Wolbachia infection from the Setariidae most likely occurred following the split that formed the Onchocercidae and Setariidae families and perhaps prior to speciation because of the members of genera Setaria, S. cervi or S. equina (Chirgwin et al, 2002) that have been investigated have not been reported to harbor Wolbachia. In contrast, the loss of Wolbachia might have occurred following speciation as has been shown to be the case in Onchocerca flexuosa of the family Onchocercidae.…”
Section: Discussionmentioning
confidence: 97%
“…(Taylor and Hoerauf 1999a). Of the various filarial species investigated using PCR and electron microscopic studies, only a fewthe rodent filariid Acanthocheilonema viteae, the deer filariid Onchocerca flexuosa (Bandi et al 1998), the human filariid Loa loa (Buttner et al 2003) and the equine filariid Setaria equina (Chirgwin et al 2002)-appear to be free of these microorganisms. The distribution and phylogenetic patterns of Wolbachia in filarial nematodes indicate that the association is stable and specific suggesting a long co-evolutionary history (Bandi et al 1998), which indicates coadaptation and reciprocal dependence between filarial nematodes and their endosymbiont (Taylor et al 2000a).…”
Section: Introductionmentioning
confidence: 97%